2020
DOI: 10.3390/s20174781
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Low Cost, Sensitive, and Portable Electrochemical Immunochromatography Sensing Device to Measure Estrone-3-Sulfate

Abstract: In livestock production, point-of-care testing (POCT) technology that enables easy on-site analysis of sex hormones is desired to improve reproductive efficiency. In this context, low-molecular-weight endogenous steroids are particularly important for perinatal management. Therefore, we attempted to use a simple method that combines electrochemical techniques with immunochromatography to measure estrone-3-sulfate (E1S), one of the low-molecular-weight endogenous steroids that is an estrogen ester. The limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These results confirmed the accuracy of the currently presented cyclic voltammetry (CV) studies. From observing CV curves, it was found that the pattern of oxidation currents reduces with increasing concentration and proved that the responses are concentration-dependent [24][25][26][27]. Here, the LFA strip test results are validated by the quantitative and qualitative determination of PCT.…”
Section: Introductionmentioning
confidence: 70%
“…These results confirmed the accuracy of the currently presented cyclic voltammetry (CV) studies. From observing CV curves, it was found that the pattern of oxidation currents reduces with increasing concentration and proved that the responses are concentration-dependent [24][25][26][27]. Here, the LFA strip test results are validated by the quantitative and qualitative determination of PCT.…”
Section: Introductionmentioning
confidence: 70%
“…For the electrochemical detection of IgG, we used our previously developed electrochemical immunochromatography platform. (10,11) The platform consists of a nitrocellulose membrane, absorbent pad, electrochemical detector, and two polymethyl methacrylate (PMMA) plates (Fig. 1).…”
Section: Electrochemical Immunochromatography Platformmentioning
confidence: 99%
“…Therefore, we previously developed an electrochemical immunochromatography platform to investigate the effects of the contact pressure and flow rate between an electrode and a nitrocellulose membrane. (9)(10)(11) Usually, electrodes are printed on a paper when an electrochemical method is introduced into µPADs. (7,12,13) In this case, the electrodes are disposable along with the paper, increasing their cost of use.…”
Section: Introductionmentioning
confidence: 99%
“…Although an electrochemical analyzer is required to obtain quantitative test results, 12 the printed electrode fills the porous membrane and obstructs the flow caused by capillary force. 13 Lee et al 14 first † These authors contributed equally and should be regarded as co-first authors of the article. a School of Information and Communication Engineering, University of Electronic Science and Technology of China, Chengdu, China.…”
Section: Introductionmentioning
confidence: 99%